Maintenance of HIV-specific CD4+ T cell help distinguishes HIV-2 from HIV-1 infection. - Duvall, MG; Jaye, A; Dong, T; Brenchley, J; Alabi, A; Jeffries, D; van der Sande, M; Togun, T; McConkey, S; Douek, D; Mcmichael, A; Whittle, H; et al. (2006)
Unlike HIV-1-infected people, most HIV-2-infected subjects maintain a healthy CD4+ T cell count and a strong HIV-specific CD4+ T cell response. To define the cellular immunological correlates of good prognosis in HIV-2 infection, we conducted a cross-sectional study of HIV Gag-specific T cell function in HIV-1- and HIV-2-infected Gambians. Using cytokine flow cytometry and lymphoproliferation assays, we show that HIV-specific CD4+ T cells from HIV-2-infected individuals maintained proliferative capacity, were not terminally differentiated (CD57-), and more frequently produced IFN-gamma or IL-2 than CD4+ T cells from HIV-1-infected donors. Polyfunctional (IFN-gamma+/IL-2+) HIV-specific CD4+ T cells were found exclusively in HIV-2+ donors. The disparity in CD4+ T cell responses between asymptomatic HIV-1- and HIV-2-infected subjects was not associated with differences in the proliferative capacity of HIV-specific CD8+ T cells. This study demonstrates that HIV-2-infected donors have a well-preserved and functionally heterogeneous HIV-specific memory CD4+ T cell response that is associated with delayed disease progression in the majority of infected people.